Copy number variation analysis and targeted NGS in 77 families with suspected Lynch syndrome reveals novel potential causative genes. Issue 11 (3rd October 2018) - Kayser, Katrin; Degenhardt, Franziska; Holzapfel, Stefanie; Horpaopan, Sukanya; Peters, Sophia; Spier, Isabel; Morak, Monika; Vangala, Deepak; Rahner, Nils; von Knebel‐Doeberitz, Magnus; Schackert, Hans K.; Engel, Christoph; et al.
Abstract : In many families with suspected Lynch syndrome (LS), no germline mutation in the causative mismatch repair (MMR) genes is detected during routine diagnostics. To identify novel causative genes for LS, the present study investigated 77 unrelated, mutation‐negative patients with clinically suspected LS and a loss of MSH2 in tumor tissue. An analysis for genomic copy number variants (CNV) was performed, with subsequent next generation sequencing (NGS) of selected candidate genes in a subgroup of the cohort. Genomic DNA was genotyped using Illumina's HumanOmniExpress Bead Array. After quality control and filtering, 25 deletions and 16 duplications encompassing 73 genes were identified in 28 patients. No recurrent CNV was detected, and none of the CNVs affected the regulatory regions of MSH2 . A total of 49 candidate genes from genomic regions implicated by the present CNV analysis and 30 known or assumed risk genes for colorectal cancer (CRC) were then sequenced in a subset of 38 patients using a customized NGS gene panel and Sanger sequencing. Single nucleotide variants were identified in 14 candidate genes from the CNV analysis. The most promising of these candidate genes were: ( i ) PRKCA, PRKDC, and MCM4, as a functional relation to MSH2 is predicted by network analysis, and ( ii ) CSMD1, as this is commonly mutated in CRC. Furthermore, six patients harbored POLE variants outside the exonuclease domain, suggesting that these might be implicated in hereditary CRC. Analyses in larger cohorts of suspected LS patients recruited via international collaborations are warranted to verify the present findings. Abstract : What's new? While several causal genetic factors for Lynch syndrome (LS), or hereditary non‐polyposis colorectal cancer, have been identified, in many families with suspected LS no germline mutation is detected during routine diagnostics. Here, a genome‐wide copy number variant (CNV) analysis in a large cohort of patients with suspected LS and MSH2 loss identified rare alterations in candidate genes ( PRKCA, PRKDC, MCM4, and CSMD1 ) that may predispose to colorectal tumorigenesis. The study demonstrates that rare germline CNVs and point mutations are likely to contribute to the hereditary risk for colorectal tumors, and the underlying genetic factors are likely to be very heterogeneous.